Analysis of the association between PTPN1 gene polymorphisms (rs941798 and rs914458) and type 2 diabetes in families from Lima – Peru - Sanchez-Castro, Enrique Eduardo (2019)
Objective: To analyze the association that PTPN1 gene single nucleotide polymorphisms (SNPs) rs941798 and rs914458 have with type 2 diabetes in Peruvian families from Lima. Materials and methods: Twenty-three (23) families consisting of three members each were recruited at the Hospital Nacional Arzobispo Loayza. Peripheral blood samples were collected to obtain the DNA, and then the allele and genotype frequencies of the SNPs. SNP genotyping was performed using the sequencing method. The family-based analysis of the association between SNPs and type 2 diabetes was conducted using the family-based association test (FBAT) program. Results: Three (3) possible genotypes were observed for each SNP, i.e. rs941798 (A>G) and rs914458 (G>C). In one of the assessed models, the family-based association tests showed at the allele level that allele A of SNP rs941798 is associated with type 2 diabetes (p = 0.023). However, after using the Bonferroni correction for multiple comparisons, this association was lost. No association was demonstrated between the SNPs and the disease at any level (allele, genotype or haplotype). Conclusions: No evidence of significant association was found between PTPN1 gene SNPs rs941798 and rs914458 and type 2 diabetes at the studied levels (allele, genotype or haplotype) in Peruvian families from Lima.